Neutral 1, 3, 5‐Triaza‐7‐phosphaadamantane‐Ruthenium(II) Complexes as Precursors for the Preparation of Highly Water‐Soluble Derivatives. Issue 17 (5th April 2016) - Battistin, Federica; Balducci, Gabriele; Iengo, Elisabetta; Demitri, Nicola; Alessio, Enzo
Abstract : The monodentate phosphane ligand 1, 3, 5‐triaza‐7‐phosphaadamantane (PTA) imparts excellent water solubility to its complexes. We aimed to prepare precursors with one or more PTA coligands for solubility and one or more labile ligands for facile replacement by a linker. For this purpose, we investigated the reactivity of the neutral isomers trans ‐ and cis ‐RuCl2 (PTA)4 (1 and2 ) towards 2, 2′‐bipyridine (bpy), as a model chelating diimine linker. The new derivatives mer ‐[Ru(bpy)Cl(PTA)3 ]Cl (9 ) and fac ‐[Ru(bpy)Cl(PTA)3 ]Cl (10 ) were prepared and characterized. We also found that PTA reacts rapidly with cis, fac ‐RuCl2 (dmso‐ O )(dmso‐ S )3 (11 ) and trans ‐RuCl2 (dmso‐ S )4 (13 ) under mild conditions through the replacement of pairs of mutually trans dmso ligands with high selectivity, even when in stoichiometric defect. Thus, 11 affords cis, cis, trans ‐RuCl2 (dmso‐ S )2 (PTA)2 (12 ), whereas13 gives1 . The two dmso ligands of12 can be replaced selectively by chelating diimines such as bpy to afford the less symmetrical all‐ cis product cis, cis ‐Ru(bpy)Cl2 (PTA)2 (16 ). Abstract : We prepared precursors with one or more 1, 3, 5‐triaza‐7‐phosphaadamantane (PTA) coligands for solubility and one or more labile ligands for facile replacement. The reactivity of trans ‐ and cis ‐RuCl2 (PTA)4 (1 and2 ) and cis, cis, trans ‐RuCl2 (dmso‐ S )2 (PTA)2 (12, dmso = dimethyl sulfoxide) towards 2, 2′‐bipyridine (bpy), as a model diamine linker, is reported.